KESADARAN HUKUM MASYARAKAT PENENUN ULOS DALAM MENDAFTARKAN HAK CIPTA MOTIF ULOS BATAK TOBA DI KOTA MEDAN - Josephine Giovana; Firdaus '; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Copy right is an exclusive right granted to creation these rights are protected by the government, the motive Ulos Batak Toba was the cultural heritage of Indonesia, which unfortunately until now has not been registered in the Directorate General Haki different with Batik Indramayu who have registered at the Directorate General of Haki, but the motive Ulos Batak Toba until now not been registered in the Directorate General Haki due to various factors, including the lack of public awareness and outreach of government.This type of research can be classified in this type of sociological research, namely the direct study on the location or point studied. This research was conducted in the city of Medan, while the sample population is a party related to the overall problem in meticulous in this study, the source of the data used are primary data and secondary data, methods of collecting data in this study with interviews and literature study. From the research there are three main issues that can be inferred. First, Ulos Batak Toba is the cultural heritage of Indonesia that has not been registered in the Directorate General of Intellectual Property Rights, which is different from the Batik Indramayu, which was registered at the Directorate General of Intellectual Property Rights and weavers Ulos Batak Toba did not know about the advantages in registering copyright motif Ulos Batak Toba in Medan; Second, the obstacles encountered was the lack of awareness of weavers Ulos Batak Toba to register copyright motif Ulos Batak Toba because there is no extension by Governments ,; Thirdly, there is less maximum cooperation between the government and the weaver Ulos Batak Toba. Suggestions Writer, first, provide information about the importance, Ulos registration Batak Toba Batak Toba expand Ulos culture and immediately register motif Ulos Batak Toba; Second, provide knowledge about the motives Ulos Batak Toba which is not only used in traditional ceremonies, but the motive Ulos Batak Toba can also be used for everyday purposes and the promotion of the Motive Ulos Batak .Keywords: Copyright-Legal Awareness-Motive Ulos Batak Toba-Weaver